Development of Nusantara Snakes and Ladders Learning Media on the Element of Bhinneka Tunggal Ika for 7th Grade at Public Middle School 3 Malang City - Pangesti, Ajeng; Kurniawan, Prima Adi; Saputra, Diky Romadoni; Wijaya, Darma Prasetya Kasenda; Sofiuddin, Ahmad; Saputro, Andrian Budi; Saputra, Meidi (International Journal of Research in Education, 2025)
This study describes the development of learning media Ular Tangga Nusantara on elements of Bhinneka Tunggal Ika class VII at Public Middle School 3 Malang City. This research uses the RnD (Research and Development) approach. The subject of this research was a small group of class VII. This research was conducted from July 2024 - October 2024. The population in this study was class VII consisting of 8 classes totaling 256 students. The sample taken by the researcher used the Solvin formula, so that 110 students were obtained to answer the questionnaire which was randomly distributed in 8 classes. The results showed a significant effect of the development of Ular Tangga Nusantara learning media on the elements of Bhinneka Tunggal Ika class VII at Public Middle School 3 Malang City can also be seen from several indicators of the questionnaire given to students after they used Ular Tangga Nusantara learning media. The indicators include the learning media Ular Tangga Nusantara proved to be able to make learning on the elements of Unity in Diversity more interesting because the learning carried out integrates fun games soas to attract the attention of students to be actively involved in learning activities.